2016
DOI: 10.29359/bjhpa.08.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Volleyball players’ somatic composition in the light of sports results at 2014 FIVB Volleyball Men's World Championship

Abstract: BackgroundThe aim of the study was to analyse sports results and the somatic composition of participants in the 2014 FIVB Volleyball Men's World Championship held in Poland. Material/MethodsResearch material involved volleyball players participating in the World Championships (n = 280). Their age, height, weight, one-arm spike reach, both-arm block reach, and Rohrer's index were analysed. The mean value of the features and their derivatives in individual teams and groups were calculated and verified using stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…The data of Castro et al [37], Papadimitriu et al [38], Jaworska et al [40], Wnorowski et al [41] on the dependence of the effectiveness of offensive actions on the speed of attack, the quality of transmission that precedes them, and the level of development of special physical qualities of athletes received further development.…”
Section: Discussionmentioning
confidence: 99%
“…The data of Castro et al [37], Papadimitriu et al [38], Jaworska et al [40], Wnorowski et al [41] on the dependence of the effectiveness of offensive actions on the speed of attack, the quality of transmission that precedes them, and the level of development of special physical qualities of athletes received further development.…”
Section: Discussionmentioning
confidence: 99%
“…Hal serupa juga disampaikan oleh (Wnorowski, & Ciemiński, 2016) Skill Atlet Voli Putra didalam permainan. Atlet yang dominan memberikan point dari skill yang ditampilkan saat pertandingan puncak memiliki kesempatan menjadi atlet terbaik.…”
Section: Pendahuluanunclassified
“…Such approaches of the authors indicate the need to find new approaches in the training of elite volleyball players [44][45][46]. Tili et al [47], Wnorowski et al [48] investigated the anthropometric data of the winners of games under the aegis of the FIVB before and after changes in the rules of the game and depending on the specialization. Other studies [49,50] have shown the effectiveness of setting the ball to qualified volleyball players in competitive conditions.…”
Section: Original Articlementioning
confidence: 99%